Analysis of Quality of Life of Teenagers with Hemophilia in Pakistan - Javed, Maryam; Hamdan, Qurrat Ulain; Azam, Usama; Ali, Nawal; Zafar, Lubna; Zafar, Tahira (Journal of Rawalpindi Medical College, 2026)
Objective: To investigate the Quality of Life (QoL) of adolescents living with hemophilia and analyze the impact of sociodemographic factors like socioeconomic status, parents’ qualification, and clinical factors like disease severity and type on their physical and psychosocial health. Methods: It was a descriptive observational study with association analysis. Fifty adolescents with either hemophilia A or B were recruited from the Hemophilia Treatment Center (HTC), managed by Hemophilia Patients Welfare Society. The Pediatric Quality of Life Inventory (PedsQL) was used to quantify QoL. Statistical analyses, including one-way ANOVA and correlations, were performed to identify associations between QoL scores and baseline factors. Results: The Majority of adolescents had compromised physical and psychosocial health. Mean Physical Health Functioning scores and Psychosocial Health Functioning scores were (44.03 ± 25.80) and (57.24 ± 18.03), respectively, which showed that both physical and psychosocial quality of life are compromised, but physical health is more affected than psychosocial health. Analysis of the association between sociodemographic variables with physical and psychosocial health yielded statistically significant results for parents’ qualification to physical and social functioning; however, the impact of clinical factors like disease severity and type did not yield statistically significant results. Conclusion: The QoL of most adolescents with hemophilia is compromised, regardless of disease severity or type. Parents’ qualification plays a positive role in adolescents’ physical and social functioning. We suggest incorporating regular psychological evaluations and parents’ psychoeducation into management plans to improve the quality of care and QoL. Keywords: Hemophilia; Adolescents; Quality of Life.